On the Study of the Informal Language of Russian Charity - Bondarenko, Elena D. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2020)
This article provides a linguistic analysis of informal nominations making part of the “thesaurus of charity”. They are lexemes that exist in the field of substandard and circulate in the environment of oral youth communication, in social networks, blogs, Internet media, etc. The main sources of the material are social networks (VKontakte), information and entertainment portals (Pikabu, YouTube, Bolshoy Vopros, etc.), as well as popular media. The informal vocabulary of charity reflects the most “popular” types of youth’s charitable activities; also, it possesses not fully established semantics and compatibility; it is often absent from any of the official explanatory dictionaries. This article focuses on words the stems донат- / донейт- / донейшн-. Analysis of the semantics and connotative background of substandard derivatives of the English verb donate make it possible to formulate some specific features of perception of the charity situation which exist in youth’s linguistic consciousness. Firstly, in the semantics of lexemes донат (and its derivatives) and донейшн, the idea of giving as a demonstration of gratitude for someone’s activities and participation in these activities is significant. Secondly, the connotative background of words with the донат- stem contains the idea of a “bonus” for the philanthropist, sometimes represented by material, but more often by moral satisfaction from the act of benefaction. Thus, the idea of giving as conscious gratitude of the donator becomes central. It seems necessary to structure the ideas about the lexical and semantic field “Gratuitous help to those in need” in order to achieve clarity in the meanings of words that make up the informal lexical field of charity and to identify the features of their compatibility with the aim of adjusting the use of substandard nominations of charitable activities in media and sociopolitical discourse.